2020
DOI: 10.2528/pierc20031402
|View full text |Cite
|
Sign up to set email alerts
|

CPW Fed Wideband Bowtie Slot Antenna on Pet Substrate

Abstract: In this article, a new wideband bowtie shaped slot antenna is realized on a flexible polyethylene terephthalate (PET). The slotted bowtie design is implemented with an asymmetric bowtie flare angle and a larger feeding neck with a metal strip inside the bowtie slot to achieve a wider bandwidth and a higher gain. The designed free space antenna is fabricated using inkjet printing and tested. The fabricated antenna operates over 2.1-4.35 GHz frequency range (69.77% fractional bandwidth) which covers WLAN, WiMax,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…They are popular and attractive in recent years for flexible electronics due to their robustness, flexibility, wettability, and stretchability. Due to high T g, polyimide is one of the most preferred materials for flexible antennas, which had been used as a substrate in prior studies [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Sanusi et al [ 55 ] reported on the design and performance of an artificial magnetic conductor (AMC)-backed dipole antenna on Kapton Polymiode for RF energy harvesting in the context of next-generation blood irradiation systems.…”
Section: Materials For Flexible Antennasmentioning
confidence: 99%
See 2 more Smart Citations
“…They are popular and attractive in recent years for flexible electronics due to their robustness, flexibility, wettability, and stretchability. Due to high T g, polyimide is one of the most preferred materials for flexible antennas, which had been used as a substrate in prior studies [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Sanusi et al [ 55 ] reported on the design and performance of an artificial magnetic conductor (AMC)-backed dipole antenna on Kapton Polymiode for RF energy harvesting in the context of next-generation blood irradiation systems.…”
Section: Materials For Flexible Antennasmentioning
confidence: 99%
“…Etching or printing slots on the flexible substrate is another way to manipulate the characteristics of the flexible antenna. [ 61 , 197 , 198 ] showed the compact, flexible antenna with slots in the patch. In another study [ 199 ], Sierpinski carpet fractal antenna on Hilbert slot pattern ground was introduced.…”
Section: Miniaturization Of Flexible Antennamentioning
confidence: 99%
See 1 more Smart Citation
“…The antenna's performance and bending effects will be discussed in part II of this work [38]. Many materials that are used in the "flexible" electronics can be considered flexible only with extremely small thicknesses (around 100um), e.g., polyimide (Kapton) [39], polyethylene [40], PTFE [41], and others [42], [7], [43]. To show the fair flexibility our polymer-based microwave devices, the substrate thickness is 3mm in all cases.…”
Section: Fabrication Techniquementioning
confidence: 99%
“…The substrate thickness is 3mm in all cases, which illustrates the flexibility with relatively high substrate thicknesses. Many materials that are used in the "flexible" electronics can be considered flexible only with minimal thicknesses (around 100um), e.g., polyimide (Kapton) [20], polyethylene [21], PTFE [22], and others [23], [7], [24].…”
Section: Fabrication Techniquementioning
confidence: 99%